An Exploration of Active Learning Strategies in Teaching English at a Junior High School with Merdeka Curriculum - Ahsani, Laili Barokatin; Susiati, S (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This qualitative study aims to obtain information on the learning model used by teachers in one of the junior high schools in Surakarta and to find out the strategies used by teachers to increase student motivation in the learning process. Methodology: This study involved 3 English teachers in one of the junior high schools in Surakarta (7th, 8th, and 9th grade English teachers) who were positioned as research subjects. All data were collected by using observation and interview methods. The collected data were analyzed descriptively in the form of continuous interaction until the data were complete. Results: The results of this study inform that the learning models that teachers use in the learning process include project-based learning models, flipped learning, and mind mapping, which are able to help teachers facilitate the learning process. The influence in the strategies that teachers do to increase student motivation to actively participate in the learning process includes conditioning the learning atmosphere, making study group discussions, holding competitive competitions, creating interesting learning variations, giving praise, and giving punishment. Applications/Originality/Value: Following up on the findings of this study, active learning strategies in the Merdeka curriculum at junior high schools in Surakarta must be further optimized through the design of lesson plans, learning resources, and learning assessments in each learning model used.